Penerapan Konsep Arsitektur Islam Kontemporer Pada Revitalisasi Islamic Centre Palaguna Di Kabupaten Wajo - Andi Rahmat Arianda; Muzdar, Muhammad Ajwad; Amin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2023)
Applying post-pandemic behavior architecture to traditional market buildings in Wajo Regency has become a forum for fulfilling trade sector activities that support programs to prevent the spread of viruses and healthy buildings. This research used the descriptive method and literature study to collect data. The research object focuses on applying contemporary Islamic architectural design to revitalize the Palaguna Islamic Center in Wajo Regency. The design results obtained are Islamic Centers that are able to support Islamic activities comfortably